One new species of the genus Acosmetura and supplement of Acosmetura emeica Liu & Zhou, 2007 (Tettigoniidae: Meconematinae) from Sichuan, China - Wang, Tao; Shi, Fu-Ming; Wang, Hai-Jian (Zootaxa, 2018)
In this paper, one new species of the genus Acosmetura Liu, 2000 is described, i.e. Acosmetura longitubera sp. nov. from Sichuan, China, and distinctive characters are illustrated. In addition, supplementary description and morphological photographs of Acosmetura emeica Liu & Zhou, 2007 from Emeishan, Sichuan are provided.